The Impact of EU Law on Hungarian Anti-discrimination Law in Employment - Halmos Szilvia (ELTE LAW JOURNAL, 2018)
The purpose of this study is to give an overview of the impact of EU law on some specific aspects of equal treatment in Hungarian labour law. In Section II, a short description is given on the main features of relevant EU and national legislation. In Section III the current status of national implementation of EU law is analysed concerning a central instrument of national equality law, i.e. the rules on burden of proof. The main developments of the case law of Hungarian courts is followed up; this was recently summarised and evaluated by the Case Law Analysing Group of the Kúria appointed to scrutinise the judicial practice of equal treatment regulation in the field of labour law. In Section IV, it is evaluated how far Hungarian labour law has come in the implementation process over the past 15 years in the analysed fields, and which challenges have to be addressed in the forthcoming 15 years.